Comparing 3 Approaches for Making Vaccine Adoption Decisions in Thailand - Waranya Rattanavipapong; Ritika Kapoor; Yot Teerawattananon; Jos Luttjeboer; Siobhan Botwright; Rachel A. Archer; Birgitte Giersing; Raymond C. W. Hutubessy (Kerman University of Medical Sciences, 2020)
Background The World Health Organization (WHO) has developed the Total System Effectiveness (TSE) framework to assist national policy-makers in prioritizing vaccines. The pilot was launched in Thailand to explore the potential use of TSE in a country with established governance structures and accountable decision-making processes for immunization policy. While the existing literature informs vaccine adoption decisions in GAVI-eligible countries, this study attempts to address a gap in the literature by examining the policy process of a non-GAVI eligible country.   Methods A rotavirus vaccine (RVV) test case was used to compare the decision criteria made by the existing processes (Expanded Program on Immunization [EPI], and National List of Essential Medicines [NLEM]) for vaccine prioritization and the TSE-pilot model, using Thailand specific data.   Results The existing decision-making processes in Thailand and TSE were found to offer similar recommendations on the selection of a RVV product.   Conclusion The authors believe that TSE can provide a well-reasoned and step by step approach for countries, especially low- and middle-income countries (LMICs), to develop a systematic and transparent decision-making process for immunization policy.